Impact of Lower Limb Active Movement Training in Individuals With Spastic Type Cerebral Palsy on Neuromuscular Control Outcomes: A Systematic Review - O'Brien, Shari M.; Lichtwark, Glen A.; Carroll, Timothy J.; Barber, Lee A. (Frontiers in Neurology, 2020)
Background: Cerebral Palsy (CP) is a non-progressive neurological condition that results in motor impairment which increases proximally to distally along the lower extremity (i.e. greatest impairment at the ankle). Consequently, poor selective motor control of lower limb joints and voluntary muscle activation results in reduced neuromuscular control in this population. CP rehabilitation traditionally aims to improve movement proficiency for functional activities, such as walking, by using a range of active movement modalities that require volitional effort; however, the underlying neural mechanisms of improved control and function remain unknown. The primary purpose of this study was to systematically determine the efficacy of lower limb active movement interventions to improve neuromuscular control in individuals with CP. Methodology: A search for studies involving an active lower limb intervention and neurophysiological outcome measures in individuals with CP was performed in five electronic databases. Studies were assessed for methodological quality using the Downs and Black assessment tool. Results: Nine of 6263 articles met the inclusion criteria. Methodological quality of all studies was poor, ranging from 2-27 out of a possible score of 32 points on the Downs and Black assessment tool. The study interventions varied extensively in modality and prescription as well as in the outcome measures used. Conclusions: Whether active movement improves neuromuscular control of the lower limb in CP is unclear due to high variability in intervention protocols and selected outcomes measures. Future active intervention studies must carefully consider the selection of neurophysiological outcome measures.